Pola Komunikasi Politik Terhadap Generasi Z Pada Pemilu 2024 - Dona Dwi Novita; Kasiana Sianipar; Ahmad Tamrin Sikumbang; Windy Sakila Nazwa; Alya Azra Mutia Nasution; Al Syahdafi; Zulkifli Zulkifli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the current era of globalization, many problems occur when entering the political era. It needs to be realized that in the current era, providing information must be in the right pattern, especially to generation Z as young people who choose. Of course, it is necessary to know the things that need to be informed to Gen Z during the political period so that the information reaches the right target to Generation Z. Therefore, it is necessary to know the political communication patterns of Generation Z, especially during the 2024 election. Understanding the communication patterns of Gen Z. one of them is by providing space for expression for them and providing two-way communication that involves them, especially during political campaigns. The goal is that generation Z no longer chooses to be part of the white group and is more involved in the progress of this nation. This research uses a qualitative method with a descriptive approach involving several generation Z people in providing information which will later be explained in written form.